Isolation of a methyl parathion-degrading Pseudomonas sp. that possesses DNA homologous to the opd gene from a Flavobacterium sp. - Chaudhry, G R (1988)
Two mixed bacterial cultures isolated by soil enrichment were capable of utilizing methyl parathion (O,O-dimethyl O-p-nitrophenylphosphorothioate) and parathion (O,O-diethyl O-p-nitrophenylphosphorothioate) as a sole source of carbon. Four isolates from these mixed cultures lost their ability to utilize the pesticides independently in transfers subsequent to the initial isolation. One member of the mixed cultures, a Pseudomonas sp., however, hydrolyzed the pesticides to p-nitrophenol but required glucose or another carbon source for growth. The crude cell extracts prepared from this bacterium showed an optimum pH range from 7.5 to 9.5 for the enzymatic hydrolysis. Maximum enzymatic activity occurred between 35 and 40 degrees C. The enzyme activity was not inhibited by heavy metals, EDTA, or NaN3. Another isolate from the mixed cultures, a Flavobacterium sp., used p-nitrophenol for growth and degraded it to nitrite. Nitrite was assimilated into the cells under conditions during which the nitrogen source was excluded from the minimal growth medium. The hybridization data showed that the DNAs from a Pseudomonas sp. and from the mixed culture had homology with the opd (organophosphate degradation) gene from a previously reported parathion-hydrolyzing bacterium, Flavobacterium sp. The use of the opd gene as a probe may accelerate progress toward understanding the complex interactions of soil microorganisms with parathions.